Do Histological Features of Eosinophilic Esophagitis in Children Correlate With Peripheral Eosinophils?. Issue 5 (May 2020) - Choudhury, Shelly; Kozielski, Rafal; Hua, Jia; Wilding, Gregory E.; Baker, Susan
ABSTRACT: Aim: Eosinophilic esophagitis (EoE) is a chronic, relapsing inflammatory disease of the esophagus. We investigate whether peripheral eosinophils can be a good indicator of esophageal eosinophilia and whether they correlate with histological findings, such as basilar hyperplasia, spongiosis, microabscesses, number of lymphocytes, and number of neutrophils. Methods: A retrospective chart review was conducted with EoE patients ages <18 years after obtaining IRB approval. Biopsies obtained from 57 EoE patients were analyzed. Patient demographics, symptoms; complete blood count with differentials obtained at the time of endoscopies or within a month of the procedure, were documented. Results: A significant correlation was observed between peripheral absolute eosinophil count (AEC) and peak esophageal eosinophil count ( P value: 0.0009). Subjects with biopsies suggestive of ongoing disease activity or active status had a higher mean of AEC at 577.41 ± 202.60 compared with subjects with inactivity with mean of 305.26 ± 526.67. However, when the subjects were broadly divided with 500 AEC as a cut off (<500 and >500 AEC), it was found that, out of 27 EoE inactive patients, 24 had AEC count less than or equal to 500 and out of 66 EoE active patients, 32 had AEC more than 500. Conclusion: Active EoE status meant a higher mean of AEC compared with inactive status; but AEC was not found to be a sensitive tool for detecting active EoE.